Entre a tradição e a inovação : Sá de Miranda na esteira de Garcilaso : em torno do debate poético da écloga Alejo - Osório, Jorge Alves (1985)
This article intends to call attention to the significance of the discussion included in Sá de Miranda's eclogue Alejo. This discussion centres on a comparison between the poetic virtualities of compositions belonging to the tradition in poetry of the «Cancioneiro» and some verse essays which follow the Italian style. The author of this article examines Sá de Miranda's thoughts on poetry both within the framework of humanist doctrine and from the point of view of the poetic tastes in courtly circles. After analysing the various textual versions of the eclogue Alejo, the author concludes that for the poet of the Neiva there existed no radical opposition between «medida velha» and «medida nova», but two different and complementary modalities of literary expression in verse.